Patterns of weight change in black Americans: Pooled analysis from three behavioral weight loss trials. (24th September 2014) - Morales, Knashawn H.; Kumanyika, Shiriki K.; Fassbender, Jennifer E.; Good, Jerene; Localio, A. Russell; Wadden, Thomas A.
<x xml:space="preserve">Abstract</x> Objective Differentiating trajectories of weight change and identifying associated baseline predictors can provide insights for improving behavioral obesity treatment outcomes. Methods Secondary, observational analyses using growth mixture models were conducted in pooled data for 604 black American, primarily female adults in three completed clinical trials. Covariates of identified patterns were evaluated. Results The best fitting model identified three patterns over 2 years: 1) mean weight loss of approximately 2 kg (n = 519); 2) mean weight loss of approximately 3 kg at 1 year, followed by ∼4 kg regain (n = 61); and 3) mean weight loss of ∼20 kg at 1 year followed by ∼4 kg regain (n = 24, with 23 from one study). In final multivariate analyses, higher BMI predicted having pattern 2 (OR [95% CI]) 1.10 [1.03, 1.17]) or 3 (OR [95% CI] 1.42 [1.25, 1.63]), and higher dietary fat score was predictive of a lower odds of having patterns 2 (OR [95% CI] 0.37[0.15, 0.94]) or 3 (OR [95% CI] 0.23 [0.07, 0.79]). Conclusions Findings were consistent with moderate, clinically non‐significant weight loss as the predominant pattern across all studies. Results underscore the need to develop novel and more carefully targeted and tailored approaches to facilitating weight loss in black American adults.